Effect of dalfampridine on information processing speed impairment in multiple sclerosis. (20th August 2019) - De Giglio, Laura; De Luca, Francesca; Gurreri, Flavia; Ferrante, Ilaria; Prosperini, Luca; Borriello, Giovanna; Quartuccio, Esmeralda; Gasperini, Claudio; Pozzilli, Carlo
Abstract : Objective: To test a possible benefit of dalfampridine on information processing speed (IPS), a key function for cognitive impairment (CogIm) in multiple sclerosis (MS). Methods: In this randomized, double-blind, placebo-controlled trial, we included patients with a score on the Symbol Digit Modalities Test (SDMT) under the 10th percentile of the reference value. Patients were randomized in a 2:1 ratio to receive dalfampridine 10 mg or placebo twice daily for 12 weeks. They underwent a comprehensive neuropsychological evaluation at screening (T0), at the end of treatment (T1), and after a 4-week follow-up (T2). The primary endpoint was improvement in SDMT. Results: Out of 208 patients screened, 120 were randomized to receive either dalfampridine (n = 80) or placebo (n = 40). At T1, the dalfampridine group presented an increase of SDMT scores vs placebo group (mean change 9.9 [95% confidence interval (CI) 8.5–11.4] vs 5.2 [95% CI 2.8–7.6], p = 0.0018; d = 0.60 for raw score; and 0.8 [95% CI 0.6–1] vs 0.3 [95% CI 0.0–0.5], p = 0.0013; d = 0.61 for z scores; by linear mixed model with robust standard error). The improvement was not sustained at T2. A beneficial effect of dalfampridine was observed in the Paced Auditory Serial Addition Test and in cognitive fatigue. Conclusion: Dalfampridine could be considered as an effective treatment option for IPS impairment in MS. Trial registration: 2013-002558-64 EU Clinical Trials Register. Classification of evidence: This study provides Class I evidence that for patients with MS with low scores on the SDMT, dalfampridine improves IPS.